Impact of the gap distance between two adjacent external windshields of a high-speed train on surrounding flow characteristics: an IDDES study. Issue 1 (31st December 2022) - Cheng, Fan; Xiong, Xiao-Hui; Tang, Ming-Zan; Li, Xiao-Bai; Wang, Xin-Ran
Abstract : The external windshield is a key component in high-speed trains for drag reduction. However, the installation gap between external windshields, which is intended for improving curve-passing ability, could lead to strong aerodynamic instability in train-end area and therefore significant operating risk for train. This study aims to advance this field based on detailed numerical simulation, investigating the related flow features in this area, particularly from a time-dependent perspective. Flow field around external windshields with different installation gaps (10, 20 and 30 mm) is resolved based on Improved Delayed Detached Eddy Simulation (IDDES). The aerodynamic forces on different windshield components, turbulent flow fields around the train-end area, and corresponding low-dimensional modes are analyzed. The results show that the difference in the external windshield gap can significantly affect the related aerodynamic forces, with the 20 mm case having the highest time-averaged values. The aerodynamic spectrum shows primary, secondary and tertiary peak frequencies with a relatively high power spectral density (PSD). Decreasing the gap distance generally increases the overall PSD in the Strouhal number ranges considered, particularly for the secondary and tertiary peaks. The load forms and their energy distributions under different external windshield gaps are obtained through the proper orthogonal decomposition analysis.